Clinical outcome of surgically treated displaced acetabular fractures with central dislocation using combined anterior and medial plating - Ahmad Radaideh; Malik Alansari Abu Tabar; Ziyad Mohaidat; Mohammad Alkhatatba; Marwan A. Ahmed (Medicinski glasnik, 2024)
Aim: Acetabular fractures are complex articular fractures with a big challenge for orthopaedic surgeons. Surgically managed displaced fractures carry favorable outcomes, especially if the articular surface is reduced accurately. This study aims to assess the clinical outcomes of surgical-ly fixed displaced acetabular fractures with central dislocation using combined anterior and medial plating. Methods: We have retrospectively evaluated sixteen patients, who had surgically managed dis-placed acetabular fractures with central dislocation at our institute. All patients underwent open reduction and internal fixation using combined anterior and medial plating via the Kocher-Langenbeck, the ilioinguinal, or the Stoppa approach. The functional outcome was assessed using the Harris Hip score. Results: Our study includes sixteen patients (12 males, 4 females) with a mean age of 35 years (range: 15-53 years). The mean follow-up was 7.8 years (range: 5-13 years). Functional outcomes were good to excellent in 12 (80%) patients and fair in 3 (20%) patients. At the final follow-up, the solid union had been achieved in all fractures, the mean HHS was 88.84 ± 7.61. Conclusion: Early reduction and surgical fixation of dis-placed acetabular fractures with central dislocation using combined anterior and medial plates appear to have good clinical outcomes.
Keywords: acetabular; bone; plates; displaced fractures